Human rights trade-offs in times of economic growth : the long-term capability impacts of extractive-led development - Valencia, Areli (Palgrave Macmillan, 2020)
Contents: Introduction: Human Rights Trade-offs in Times of Economic Growth: A Tale from PeruChapter 1: The La Oroya Conflict: The Intractable Conflict between Health and WorkChapter 2: A Systemic Human Rights Model of Analysis: An Integrated ApproachChapter 3: Systemic Lack of Freedom in La Oroya: The Socio-Historical Rootsand the Political-Economic BackgroundChapter 4: Experiencing Systemic Lack of Freedom: The Voice of La OroyaChapter 5: Examining the Trade-offs between Health and Work in La Oroya: The Long-term Capability Impacts of Extractive-led DevelopmentConclusion: La Oroya at the CrossroadsBibliographyAppendix 1.